Economic substance requirements and multinational firm behavior - Aparna Mathur; Kartikeya Singh (American Enterprise Institute (AEI), 2017)
Singh and Mathur find that the emphasis on the OECD's concept of "economic substance" can have a significant impact on the scale as well as the location of economic activity and likely has highly unfavorable implications on economic activity for high-tax jurisdictions. Viewed from a U.S. perspective, this new international environment provides one more impetus to strive for a reform of the corporate tax code to make it more competitive.
Keywords: A; 330; tax reform; corporate taxes; Organization for Economic Co-operation and Development (OECD)